A short history from Karelia study to biodiversity and public health interventions - Haahtela, Tari; Alenius, Harri; Auvinen, Petri; Fyhrquist, Nanna; von Hertzen, Leena; Jousilahti, Pekka; Karisola, Piia; Laatikainen, Tiina; Lehtimäki, Jenni; Paalanen, Laura; Ruokolainen, Lasse; Saarinen, Kimmo; et al. (Frontiers in Allergy, 2023)
Contact with natural environments enriches the human microbiome, promotes immune balance and protects against allergies and inflammatory disorders. In Finland, the allergy & asthma epidemic became slowly visible in mid 1960s. After the World War II, Karelia was split into Finnish and Soviet Union (now Russia) territories. This led to more marked environmental and lifestyle changes in the Finnish compared with Russian Karelia. The Karelia Allergy Study 2002–2022 showed that allergic conditions were much more common on the Finnish side. The Russians had richer gene-microbe network and interaction than the Finns, which associated with better balanced immune regulatory circuits and lower allergy prevalence. In the Finnish adolescents, a biodiverse natural environment around the homes associated with lower occurrence of allergies. Overall, the plausible explanation of the allergy disparity was the prominent change in environment and lifestyle in the Finnish Karelia from 1940s to 1980s. The nationwide Finnish Allergy Programme 2008–2018 implemented the biodiversity hypothesis into practice by endorsing immune tolerance, nature contacts, and allergy health with favorable results. A regional health and environment programme, Nature Step to Health 2022–2032, has been initiated in the City of Lahti, EU Green Capital 2021. The programme integrates prevention of chronic diseases (asthma, diabetes, obesity, depression), nature loss, and climate crisis in the spirit of Planetary Health. Allergic diseases exemplify inappropriate immunological responses to natural environment. Successful management of the epidemics of allergy and other non-communicable diseases may pave the way to improve human and environmental health.